2021
DOI: 10.1186/s12909-021-02857-8
|View full text |Cite
|
Sign up to set email alerts
|

Flexible e-learning video approach to improve fundus examination skills for medical students: a mixed-methods study

Abstract: Background Training for the fundus examination using traditional teaching is challenging, resulting in low generalist physicians’ confidence in performing the funduscopic examination. There is growing evidence suggesting a flexible e-learning video approach’s value in teaching physical examination procedures. However, whether the flexible e-learning video approach is superior to the traditional, face-to-face (F2F) lecture-based teaching for the funduscopic exam and the cognitive processes suppo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
1
9
0
1
Order By: Relevance
“…In this research, content analysis identified a total of nine categories and 17 subcategories corresponding to four levels of the revised Bloom's taxonomy; and the most frequent subcategory by the number of codes was applyin the flipped classroom approach. A study that evaluated the educational effects of flipped classroom method using a modified version of Bloom's Taxonomy also found equivalent results [36]. Mastering a common language, understanding basic knowledge, and practicing applications in simulations may be the factors that have been effective.…”
Section: Discussionmentioning
confidence: 97%
“…In this research, content analysis identified a total of nine categories and 17 subcategories corresponding to four levels of the revised Bloom's taxonomy; and the most frequent subcategory by the number of codes was applyin the flipped classroom approach. A study that evaluated the educational effects of flipped classroom method using a modified version of Bloom's Taxonomy also found equivalent results [36]. Mastering a common language, understanding basic knowledge, and practicing applications in simulations may be the factors that have been effective.…”
Section: Discussionmentioning
confidence: 97%
“…It appears that the utility of e-learning transcends that of providing medical students with lectures in different formats but was also shown to be effective in promoting technical skills. The body of literature shows promising results across the following topics: laboratory skills [43], electrocardiogram visualization and interpretation [44], chronic wound management [45], fundus examination [46], and general ward examination skills (e.g., cannulation, physical examination) [47]. It should be noted that the effectiveness of teaching such skills must be within a blended/hybrid context between e-learning and traditional feedback teaching.…”
Section: Discussionmentioning
confidence: 99%
“…22 The transcripts were analyzed using deductive content analysis, drawing upon the stress factors and stress-coping methods as the coding frame with the cognitive process dimensions as the theme categories and subcategories. 23,24 Two authors (TM and KS) performed the open coding of stress factors, and two authors (MS and KS) performed the open coding of stress-coping methods. They independently read and coded all the transcripts.…”
Section: Discussionmentioning
confidence: 99%